2003
DOI: 10.1007/s00405-001-0440-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of nasal haemangiopericytoma

Abstract: Haemangiopericytomas are vascular tumours derived from Zimmerman's pericytes; they account for about 1% of all vascular tumours. About 5% of the cases occur in the nasal cavity and usually show well-differentiated tumours with low potential for local recurrence or metastasis. The treatment of choice is surgical resection. We present a case of nasal haemangiopericytoma treated by endoscopic resection, and we emphasise the advantages of this minimally invasive method compared with traditional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
0
19
0
3
Order By: Relevance
“…Although only histology can find the final diagnosis [23, 24], biopsy is not recommended as it may lead to severe bleeding [20, 25]. Therefore, radiological examination by CT and/or MRI should preferentially be performed.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Although only histology can find the final diagnosis [23, 24], biopsy is not recommended as it may lead to severe bleeding [20, 25]. Therefore, radiological examination by CT and/or MRI should preferentially be performed.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Only a few years ago, an external surgical approach, usually via lateral rhinotomy, was considered as the standard treatment regimen [22, 24] and was even regarded as obligatory when the tumor breached the cribriform plate [30] or spread beyond the sinonasal region [24]. An elective neck dissection is not indicated as lymphogenous metastases occur rarely [29].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of relative radioresistance, the mainstay of treatment is wide surgical excision . Several studies have also shown the utility of adjuvant radiotherapy, especially in cases where complete resection is not possible . Although traditional surgical management involved open surgical approach, endoscopic resection of these lesions is gaining support, and has consistently shown favorable results .…”
mentioning
confidence: 99%